Advanced treatment techniques for industrial wastewater - Hussain, Athar 1976-; Ahmed, Sirajuddin 1967- (IGI Global, Disseminator of Knowledge, 2019)
"This book addresses topics in Industrial wastewater treatment and disposal. It will cover the different aspects of environmental engineering related to water and wastewater treatment processes and systems and control studies as well as solid and hazardous waste management emerging from such industries"--
Keywords: Sewage disposal; Factory and trade waste; Aufsatzsammlung